Learning Large Lessons The Evolving Roles of Ground Power and Air Power in the Post-Cold War Era - Johnson, David E. (RAND Corporation, 2007)
The relative roles of U.S. ground and air power have shifted since the end of the Cold War. At the level of major operations and campaigns, the Air Force has proved capable of and committed to performing deep strike operations, which the Army long had believed the Air Force could not reliably accomplish. If air power can largely supplant Army systems in deep operations, the implications for both joint doctrine and service capabilities would be significant. To assess the shift of these roles, the author of this report analyzed postÂ-Cold War conflicts in Iraq (1991), Bosnia (1995), Kosovo (1999), Afghanistan (2001), and Iraq (2003). Because joint doctrine frequently reflects a consensus view rather than a truly integrated joint perspective, the author recommends that joint doctrine-and the processes by which it is derived and promulgated-be overhauled. The author also recommends reform for the services beyond major operations and campaigns to ensure that the United States attains its strategic objectives. This revised edition includes updates and an index.